The Influence of the School Library on Mathematics Learning Achievement of Grade III Students in the First Trimester at Escola Básica Central 3º Ciclo Vasco da Gama Manatuto in the 2014 Academic Year - Antonio Guterres; Bernardino de Castro; Tonico de Jesus (Eduvest - Journal of Universal Studies, 2024)
The library is one of the contributing factors or a supporting tool in the educational process at schools, ranging from elementary to higher education levels. A school library is any library organized within a school, where it is essential to have books that support and serve as references for students. The school library plays a vital role in supporting the educational process, providing essential resources for students to enhance their knowledge and complete assignments. This study explores the impact of library usage on the mathematics achievement of Grade III students at Escola Básica Central Vasco Da Gama Manatuto during the first trimester of the 2014 academic year. The research questions focus on whether the library influences mathematics achievement and if students who use the library perform better than those who do not. The study involved 112 students, with a sample of 56, and utilized parametric statistical analysis. The results showed a significant influence of library use on mathematics achievement, with a determination coefficient of 36.72%, meaning that library utilization contributes significantly to students' performance in mathematics, while the remaining 63.28% is influenced by other factors. The t-test results confirmed that students who used the library performed better in mathematics than those who did not. Based on these findings, the author suggests that students should be encouraged to utilize library resources effectively, the government should prioritize the development of school libraries, and librarians should provide welcoming and supportive service to students.